Economics and History: Surveys in Cliometrics - Greasley, D.; Oxley, Leslie (2011)
Economics and History presents six state-of-the-art surveys from some of the leading scholars in cliometrics. The contributions are all written at an accessible level for the non-specialist reader and consider a broad range of issues from this highly topical area. Written clearly and comprehensively, allowing easy accessibility for the non-specialist reader Brings together the very latest research in this highly topical subject from leading scholars Contributions cover a broad range of areas within this subject The latest publication in the highly successful Surveys ofRecent Research in Economics Book Series. © Chapters © 2011 The Authors Book compilation © 2011 Blackwell Publishing Ltd.